OPTIMIZATION OF PREVENTIVE THRESHOLD FOR CONDITIONBASED MAINTENANCE OF RADIO ELECTRONIC EQUIPMENT - Solomentsev , O. V.; Zaliskyi , M. Yu.; Shcherbyna , O. A.; Asanov , M. M. (Radio Electronics, Computer Science, Control, 2021)
Context. Operation costs throughout the life cycle of radio electronic equipment are very significant, which value far exceeds the initial cost of the equipment. Therefore, the up-to-date scientific and technical problem is to minimize operation costs. One of the ways to solve this problem is the introduction of statistical data processing technologies in the operation systems of radio electronic equipment. Objective. The goal of the paper is to improve the efficiency of thecondition-based maintenance with the determining parameters monitoring, which is widely used in civil aviation. Method. The solution of this problem is based on finding the functional dependence of the efficiency indicator in the form of specific operation costs on the basic parameters of radio electronic equipment and its operation system. To determine this dependence, the probability-event model is used,as well as methods of probability theory and mathematical statistics, in particular methods of statistical classification of sample sets and functional transformations of random variables. To determine the optimal level of the preventive threshold by the criterion of minimizing operation costs, the method of statistical simulation of Monte-Carlo is used. Results. Maintenance strategy with the determining parameters monitoring based on additional statistical data processing and technology of the optimal preventive threshold calculation are improved. Conclusions. The obtained results can be used during the development and modernization of operation systems of radio electronic equipment in terms of application of statistical data processing procedures. A comparative analysis of the two maintenance strategies showed that the use of additional statistical data processing might reduce specific operation costs. The proposed technology for determining the optimal preventive threshold can be extended to use during the operation of complex technical systems, in particular for those whose technical condition is associated with the values of the determining parameters.